Sintesis Koloid Nanopartikel Bismut: Peran Citrus limon dan Optimasi Daya serta Waktu Pemanasan Gelombang Mikro - Utami, Ni Wayan Mega Savira; Wahyuna Nur; Sukmawati Said (Universitas Islam Negeri Alauddin Makassar, 2025)
This study successfully synthesized bismuth nanoparticle colloids using citrus limon extract through a microwave heating method. Microwave heating was used as the main factor controlling the particle formation process, so variations in power and heating time were examined to determine their effect on the characteristics of the resulting nanoparticles. The synthesis was carried out by dissolving bismuth powder (Bi(NO₃)₃·5H₂O) into citrus limon extract. The mixture was then heated using microwaves at powers of 100, 300, 450, 600, and 800 W for 1, 3, 5, 7, and 10 minutes. Characterization was performed using UV-Vis, XRD, and TEM to observe the optical properties, crystal structure, and particle morphology and size. The results show that the optimum condition was achieved at 800 W for 5 minutes, marked by a change in the color of the solution to black and maximum absorbance at a wavelength of 272 nm (2,680 a.u.). XRD analysis showed diffraction peaks at 2θ = 27.4°; 38.1°; and 40.0°, corresponding to the hkl planes (012), (104), and (110), confirming the characteristic trigonal crystalline structure of bismuth based on JCPDS standard No. 44-1246. TEM images show a dominant spherical particle morphology with an average size of 33.19 nm. These results prove that microwave heating is capable of accelerating and stabilizing the synthesis of citrus limon extract-based bismuth nanoparticle colloids, producing stable nanoparticles with good morphology.